2015
DOI: 10.1371/journal.pone.0115331
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of the Capsid Gene during a Genotype II.4 Dominated Norovirus Season in One University Hospital: Identification of Possible Transmission Routes

Abstract: Norovirus (NoV) is a leading cause of gastroenteritis and genotype II.4 (GII.4) is responsible for the majority of nosocomial NoV infections. Our objective was to examine whether sequencing of the capsid gene might be a useful tool for the hospital outbreak investigation to define possible transmission routes. All NoV positive samples submitted from one university hospital during the 2007/8 season were selected. Genotyping of selected samples by partial polymerase gene sequencing had shown that the majority be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
1
9
1
1
Order By: Relevance
“…Moreover, nosocomial transmission and outbreaks have been linked to immunodeficient patients [4143]. Although several patients in our study showed evidence of chronic infection with the same virus genotype over sustained periods, we did not find evidence of transmission of these specific strains within the NIH Clinical Center.…”
Section: Discussioncontrasting
confidence: 58%
“…Moreover, nosocomial transmission and outbreaks have been linked to immunodeficient patients [4143]. Although several patients in our study showed evidence of chronic infection with the same virus genotype over sustained periods, we did not find evidence of transmission of these specific strains within the NIH Clinical Center.…”
Section: Discussioncontrasting
confidence: 58%
“…A BLAST search revealed 99% identity with multiple GII.4 Den Haag variants from Australia, Japan, Taiwan, and Korea isolated during the 2006 to 2007 period. This result supports the conclusion that closely related GII.4 2006b variants were circulating not only in the United States, but also in multiple areas worldwide in 2006 and 2007 ( 9 13 ).…”
Section: Genome Announcementsupporting
confidence: 88%
“…Overall, we observed that some regions of the NoV genomes are particularly prone to mutation (variant frequency > 5%). It has also been demonstrated that during direct viral transmissions minor variants within the donor viral quasispecies can present as major variants or consensus sequences in the recipient viral population (Kundu et al, 2013 ; Holzknecht et al, 2015 ). Therefore, epidemiological data together with deep WGS data obtained from linked cases and transmission chains can provide efficient means for source attribution and may help to identify signatures and patterns in the mutations throughout the viral genomes.…”
Section: Discussionmentioning
confidence: 99%